Comparison of Proximate Composition of Coconut Dregs Flour Produced by Dry and Wet Processes as an Alternative to Wheat Flour - Endah Sulistiawati; Imam Santosa (Indonesian Journal of Chemical Engineering, 2025)
Currently, Indonesia relies on wheat imports to meet its domestic flour demand. In contrast, the country is rich in local agricultural resources, particularly coconuts. Substantial amounts of coconut dregs are discarded during the production of coconut milk and coconut oil, contributing to environmental pollution. This study explored the conversion of coconut dregs into flour using two processing methods: dry and wet. The dry method involved grating fresh coconut meat, roasting it at 80-100 °C, and pressing to extract the oil, producing coconut dregs as a byproduct. The wet method involved grating fresh coconut meat, mixing it with water, and filtering to make coconut milk, with the coconut dregs as a byproduct. Subsequently, the coconut dregs were dried by roasting (80-100 °C), then grinding and screening. Coconut dregs flour was subjected to proximate analysis to determine its water, ash, protein, fat, and carbohydrate content. In this study, a proximate analysis was conducted on wheat flour for comparison. Coconut dregs flour from the dry process contained 53.40% fat, 9.45% protein, and 32.62% carbohydrate. The wet process produced flour with a fat content of 36.47%, protein 0.36%, and carbohydrate 55.08%. The wheat flour contained 1.11-2.10% fat, 0.6-1.1% protein, and 84.28%-86.05% carbohydrate. Coconut dreg flour could be combined with other flours to create nutritious food options, thereby reducing reliance on wheat flour.